Science and Football VIII The Proceedings of the Eighth World Congress on Science and Football - Elbe, Anne-Marie; Pfister, Gertrud; Ottesen, Laila; Krustrup, Peter; Riis Hansen, Peter; Bangsbo, Jens (Taylor & Francis, 2017)
Science;Football;Congresses;Physiological;Soccer